A família escrava nos livros didáticos de história - Almeida, Gabriela Santos (2023)
This dissertation aimed to analyze how the 7th and 8th grade History textbooks for Elementary School approved by the PNLD of 2020 address issues such as the existence of slave families, slave resistance to captivity, the participation of slaves in social movements and their participation in the abolitionist struggle, based on recent historiographical discussions. First, an overview of the historiography on slavery in Brazil and the main historiographical tendencies on the subject are presented. Next, the content of the textbooks is examined. From the reading and analysis of the books, it can be seen that the great majority of the approved textbooks present and are based on recent historiographical studies, however many do not address, or address very briefly, the existence of slave families. And it is taking into account this gap, that the “Manual Didático – FAMÍLIA E AFETIVIDADE ESCRAVA NO SÉCULO XIX" is proposed. In this material, I have tried to present support texts and suggestions of periodical sources for teachers to approach in class the various types of family constitution and affectivity among slaves. Besides, in this material I also try to present the trajectory of the historiography about the theme in Goiás.